Redefining Humicola sensu stricto and related genera in the Chaetomiaceae - Wang, X.W. (Stud Mycol, 2018)
The traditional concept of the genus Humicola includes species that produce pigmented, thick-walled and single-celled spores laterally or terminally on hyphae or minimally differentiated conidiophores. More than 50 species have been described in the genus. Species commonly occur in soil, indoor environments, and compost habitats. The taxonomy of Humicola and morphologically similar genera is poorly understood in modern terms. Based on a four-locus phylogeny, the morphological concept of Humicola proved to be polyphyletic. The type of Humicola, H. fuscoatra, belongs to the Chaetomiaceae. In the Chaetomiaceae, species producing humicola-like thick-walled spores are distributed among four lineages: Humicola sensu stricto, Mycothermus, Staphylotrichum, and Trichocladium. In our revised concept of Humicola, asexual and sexually reproducing species both occur. The re-defined Humicola contains 24 species (seven new and thirteen new combinations), which are described and illustrated in this study. The species in this genus produce conidia that are lateral, intercalary or terminal on/in hyphae, and conidiophores are not formed or are minimally developed (micronematous). The ascospores of sexual Humicola species are limoniform to quadrangular in face view and bilaterally flattened with one apical germ pore. Seven species are accepted in Staphylotrichum (four new species, one new combination). Thick-walled conidia of Staphylotrichum species usually arise either from hyphae (micronematous) or from apically branched, seta-like conidiophores (macronematous). The sexual morph represented by Staphylotrichum longicolleum (= Chaetomium longicolleum) produces ascomata with long necks composed of a fused basal part of the terminal hairs, and ascospores that are broad limoniform to nearly globose, bilaterally flattened, with an apical germ pore. The Trichocladium lineage has a high morphological diversity in both asexual and sexual structures. Phylogenetic analysis revealed four subclades in this lineage. However, these subclades are genetically closely related, and no distinctive phenotypic characters are linked to any of them. Fourteen species are accepted in Trichocladium, including one new species, twelve new combinations. The type species of Gilmaniella, G. humicola, belongs to the polyphyletic family Lasiosphaeriaceae (Sordariales), but G. macrospora phylogenetically belongs to Trichocladium. The thermophilic genus Mycothermus and the type species My. thermophilum are validated, and one new Mycothermus species is described. Phylogenetic analyses show that Remersonia, another thermophilic genus, is sister to Mycothermus and two species are known, including one new species. Thermomyces verrucosus produces humicola-like conidia and is transferred to Botryotrichum based on phylogenetic affinities. This study is a first attempt to establish an inclusive modern classification of Humicola and humicola-like genera of the Chaetomiaceae. More research is needed to determine the phylogenetic relationships of “humicola”-like species outside the Chaetomiaceae.